EFFECT OF PLANNING, IMPLEMENTATION, SUPERVISION AND CONTROLLING, BUREAUTRATION STRUKTURE AND SYSTEMS INFORMATION ON MANAGEMENTOF GOODS REGIONSWITH COMMUNICATION AS A MODERATINGVARIABLE IN DISTRICT GOVERMENT - Oktavia, Suriana (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of planning, implementation, supervision and control, bureaucratic structure, and information system on the management of regional government’s property with communication as moderating variable in the SerdangBedagai District Administration. The research used causal method, using primary data with questionnaires. The population was 141 respondents, and all of them were used as the samples. The data were analyzed by using multiple linear regression analysis and residual test for testing moderating variable. The result of the research showed that showed that, simultaneously, planning, implementation, supervision and control, bureaucratic structure, and information system had significant influence on the management of regional government’s property. Partially, implementation, bureaucracy structure, and information system had positive and significant influence on the management of regional government’s property. Meanwhile, planning, supervision, and control had positive and insignificant influence on the management of regional government’s property. The variable of communication could not moderate the correlation of planning, implementation, supervision and control, bureaucratic structure, and information system with the management of regional government’s property.